2017
DOI: 10.1080/01462679.2017.1299657
|View full text |Cite
|
Sign up to set email alerts
|

Weeding with Wisdom: Tuning Deselection of Print Monographs in Book-Reliant Disciplines

Abstract: As university libraries transition to digital collections and new services, their book deselection projects often lead to the adoption of cross-discipline quantitative weeding criteria (such as age and low circulation) in the interest of speed and presumed fairness. Cross-discipline quantitative rubrics, however, can have unintended negative consequences when applied to disciplines such as history and literature that rely on older books with low circulation statistics. The authors argue for a discipline-differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…A relatively smaller library, one that had to relocate and/ or remove newer books, or one that had to remove a greater percentage of its collections could well experience different outcomes. It is possible that a project that relocated and/or "weeded" more humanities and social sciences books would produce different outcomes (McAllister & Scherlen, 2017). Thus, the results of this study are not generalizable, nor does the study provide deep causal explanations for the effects observed.…”
Section: Limitations To the Studymentioning
confidence: 72%
“…A relatively smaller library, one that had to relocate and/ or remove newer books, or one that had to remove a greater percentage of its collections could well experience different outcomes. It is possible that a project that relocated and/or "weeded" more humanities and social sciences books would produce different outcomes (McAllister & Scherlen, 2017). Thus, the results of this study are not generalizable, nor does the study provide deep causal explanations for the effects observed.…”
Section: Limitations To the Studymentioning
confidence: 72%
“…Many librarians mistakenly believe this is simply an emotional attachment that must be handled through better public relations or achieving faculty "buy-in" (Agee, 2017;Lynd, 2015;Metz & Gray, 2005;Young, 2009). While public relations are important for any library project, the presenters' research has shown that the concerns expressed by faculty during such projects are thoughtful and reasonable (McAllister & Scherlen, 2017). During the main stacks weeding project at their mid-sized academic library, the presenters discovered that many low-use print monographs are still both relevant and needed by humanities scholars.…”
Section: Research and Case Studymentioning
confidence: 99%
“…The presenters summarized their extensive literature review on monographic research methods of humanities scholars and on the history of print book deselection in academic libraries, which was published recently in Collection Management entitled "Weeding with Wisdom: Tuning Deselection of Print Monographs in Book-Reliant Disciplines" (McAllister & Scherlen, 2017). The presenters discovered that many academic libraries are employing quantitative weeding criteria across disciplines in the interest of speed and presumed "fairness," but in fact may be overlooking the research needs of scholars in the humanities and humanities-like areas of the social sciences for ready access to low-circulation print books.…”
Section: Introductionmentioning
confidence: 99%
“…Material age and lack of recent circulation are often suggested as fair and objective means to inform these decisions, particularly in disciplines that rely heavily on recent materials, but these factors may be less meaningful in disciplines that rely on older, low-use material. 13 A 2013 SPEC Kit on print retention in Association of Research Libraries suggested duplication as the most likely factor for deaccession among surveyed libraries. 14 Libraries may also consider factors such as local or historical interest, availability of materials from other libraries, inclusion on core title lists, notability of authors, curricular needs or program alignment, value, and faculty input in refining these criteria.…”
Section: Data and Decision-makingmentioning
confidence: 99%